WACANA INTELEKTUAL KEISLAMAN DI INDONESIA DENGAN TIMUR TENGAH - Faizal Lubis; Aidil Azhar Faizal Lubis (Jurnal Bilqolam Pendidikan Islam, 2025)
The intellectual relationship between Indonesia and the Middle East has existed since the early spread of Islam in the Indonesian archipelago through trade, missionary activities, education, and scholarly networks. This interaction not only contributed to the dissemination of Islam but also shaped an intellectual tradition that significantly influenced the development of Islamic education, thought, and institutions in Indonesia. This study aims to describe the forms of Islamic intellectual discourse that emerged from the interaction between Indonesia and the Middle East. The research employed a qualitative approach using a library research method. Data were collected from books, scientific journals, historical documents, and other relevant literature, and were analyzed using content analysis techniques. The findings reveal that this intellectual relationship gave rise to various developments in Islamic scholarship, including the establishment of the Nusantara-Haramayn scholarly network, the harmonization of Islamic jurisprudence and Sufism, the development of the Kitab Kuning tradition, the emergence of influential works by Nusantara scholars, the establishment of Islamic educational institutions such as pesantren, the growth of neo-Sufism, and the expansion of Islamic brotherhoods (tarekat) throughout Indonesia. These findings indicate that the intellectual dynamics of Islam in Indonesia are the result of a synthesis between Middle Eastern scholarly traditions and local cultural values, creating a moderate, adaptive, and sustainable Islamic intellectual tradition.